2019
DOI: 10.30607/kvj.615875
|View full text |Cite
|
Sign up to set email alerts
|

The New Mastitis Agents Emerged in Cattle in Turkey and An Investigation of Their Antimicrobial Susceptibility

Abstract: There are new emerging cattle mastitis agents that have become a major burden economically on the dairy industry because of their negatively affects on production and quality in dairy cattle farming in Turkey,. To overcome this emerged problem, antimicrobials are adopted in this sector to prevent and administrate mastitis and other bacterial infections affecting cattle in the country. Nevertheless, the occurrence of antimicrobial resistance (AMR) is increasing in both animal and human contaminants. The occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Milk samples were bacteriologically examined according to the procedure previously described (Kenar et al, 2019). After reaching to the laboratory milk samples were aseptically removed from the cooler box for examination.…”
Section: Bacteriological Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk samples were bacteriologically examined according to the procedure previously described (Kenar et al, 2019). After reaching to the laboratory milk samples were aseptically removed from the cooler box for examination.…”
Section: Bacteriological Assaysmentioning
confidence: 99%
“…Kenar et al (2019) identified 11 characterized Gram (+) organisms from 61 milk samples of cattle. In addition 50 isolates of Gram (-) fermenting and nonfermenting Burkholdria and B. pseudomallei were screened by Gram stain.…”
mentioning
confidence: 99%